Respuesta :

Given the Quadratic Expression:

[tex]5x{}^2-11x+2[/tex]

You can identify that it has this form:

[tex]ax^2+bx+c[/tex]

Then, you can use the Quadratic Formula to find its x-intercepts:

[tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]

In this case:

[tex]\begin{gathered} a=5 \\ b=-11 \\ c=2 \end{gathered}[/tex]

Therefore, by substituting values into the formula and evaluating, you get:

[tex]x=\frac{-(-11)\pm\sqrt{(-11)^2-4(5)(2)}}{2(5)}[/tex][tex]x_1=\frac{11+\sqrt{81}}{10}=2[/tex][tex]x_2=\frac{11-\sqrt{81}}{10}=\frac{1}{5}[/tex]

Knowing the x-intercepts, you can write the expression in Factored Form:

[tex]=(x-2)(5x-1)[/tex]

Hence, the answer is:

[tex]=(x-2)(5x-1)[/tex]

RELAXING NOICE
Relax